DETERMINATION OF SOLUBLE EXTRACTIVE OF SOME MEDICINAL PLANTS OF GENUS SESBANIA OF MARATHWADA REGION IN MAHARASHTRA: Life Science-Botany - R.K.MOMIN; KADAM V.B. (International Journal of Life Science and Pharma Research, 2012)
The seasonal variation of water soluble extractive alcohol soluble extractive and ether soluble extractive have been investigated in leaves, wood and bark of Sesbania grandiflora, Sesbania bispinosa and Sesbania cannabina. Comparative account of water soluble extractive of leaves, wood and bark of Sesbania grandiflora was showed high level (range 4.2 to 5.8 %) than Sesbania bispinosa (range 3.3 to 5.6 %) and Sesbania cannabina (range 2.3 to 3.6 %) in all seasons. Alcohol soluble extractive of leaves of Sesbania grandiflora showed higher (range 6.15 to 6.85 %) and lower in bark of Sesbania cannabina (range 2.85 to 3.7 %). Ether soluble extractive of leaves of Sesbania grandiflora showed higher (range 4.3 to 4.55 %) and lower in bark of Sesbania cannabina (range 1.85 to 2.8 %).